Analysis of the Al-PANI interfaces by complex impedance spectroscopy - Cazati, T.; Maciel, A. C.; Eiras, C.; Constantino, C. J. L. [UNESP]; da Cunha, H. N.; Bianchi, R. F. (Iop Publishing Ltd, 2011)
This paper describes a new approach to improve the analysis of surface modification of free-standing semiconducting polymer films emerged from the interfacial interaction between aluminium electrode and HCl-doped polyaniline (PANI) films. The Al-PANI-Al structure was prepared by casting PANI/N-methyl-2-pirrolidone onto a glass substrate and then being sandwiched between Al electrodes after immersion in HCl aqueous solutions and then dried. The Al-polymer interface was investigated by means of complex impedance spectroscopy in the frequency domain on HCl-doped PANI films. The dc conductivity of the interfacial layer between the Al and PANI surface exposed to air during the film processing is higher than those obtained with Al and PANI surface exposed to glass. Raman spectroscopy data confirm this evidence. Here, it is speculated that some dissociated chlorine and aluminium-salt-containing species have contributed as ionic carriers increasing the electrical conductivity of the polymer bulk, and by the formation of an Al(2)O(3) thin layer between the Al and PANI films. An equivalent circuit model considering the influence of Al-PANI reactions on the electrical behaviour of the Al-PANI-Al structure was proposed. Additionally, it was demonstrated that the impedance spectroscopy facilitates the identification of interface modification in the Al-PANI-Al films.